Screening of Apiaceae fruits discovered natural resources with considerable biological potential - Zahra Tofighi; Mostafa Pirali Hamedani; Saeed Tavakoli; Mir Javad Tabatabaei; Marzieh Rabei; Shamim Mohtadi; Farnoosh Mirghaffari; Maryam Afshani; Farhad Kahrizi; Behruz Khodabandeloo; Saeede Jafari-Nodooshan; Mahdieh Shirzad; et al. (Institue of Medicinal Plants, ACECR, 2020)
Background: Apiaceae fruits as common spices used for prevention of many chronic diseases including cancer. Objective: The present study compared the biological effects of different fruits from various Apiaceae tribes to compare and find the fraction source(s) with potential characteristics for further investigation including cancer prevention. Methods: Fruits of Apium graveolens L. (celery), Bunium persicum (Boiss.) B.Fedtsch. (black cumin), Petroselinum crispum (Mill.) Fuss (parsley), Pimpinella anisum L. (anise), Trachyspermum ammi (L.) Sprague (ajwain), Coriandrum sativum L. (coriander), Foeniculum vulgare Mill. (fennel), Anethum graveolens L. (dill), Heracleum persicum Desf. ex Fisch., C.A.Mey. & Avé-Lall. (Persian hogweed), Ferula assa-foetida L. (asafoetida), Cuminum cyminum L. (cumin) and Daucus carota L. (carrot) were extracted with 80 % methanol and fractionated by petroleum ether, chloroform, ethyl acetate and methanol, respectively. For different fractions and total extract of all 12 samples, cytotoxicity by brine shrimp test (BST) and MTT assay against cancer and normal cell (foreskin fibroblast cells), antioxidant effects by FRAP, and total phenols by Folin-Ciocalteu method were measured. Results: The general toxicity of ethyl acetate fractions (mean of data) was higher than others in the brine shrimp test (P < 0.05). The most cytotoxic fractions against colon carcinoma (HT-29), breast adenocarcinoma (MDA-MB-231) and alveolar basal epithelial adenocarcinoma (A549) cell lines were from Ammineae and Peucedaneae tribes while fruits fractions with high phenol contents and antioxidant powers were from Ammineae tribe. Conclusion: The Apiaceae fruits have significant biological effects, therefore the isolation of phytochemical compounds from active fractions with cytotoxicity is suggested in future studies.